2011
DOI: 10.1111/j.1365-3040.2011.02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione in plants: an integrated overview

Abstract: Plants cannot survive without glutathione (g-glutamylcysteinylglycine) or g-glutamylcysteinecontaining homologues. The reasons why this small molecule is indispensable are not fully understood, but it can be inferred that glutathione has functions in plant development that cannot be performed by other thiols or antioxidants. The known functions of glutathione include roles in biosynthetic pathways, detoxification, antioxidant biochemistry and redox homeostasis. Glutathione can interact in multiple ways with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
936
3
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,276 publications
(996 citation statements)
references
References 323 publications
13
936
3
16
Order By: Relevance
“…The GSTs in plants have antioxidant properties that can scavenge ROS and other toxic compounds, maintain redox homeostasis, and mediate biosynthesis of certain defense molecules; however, specific function vary by the class [66][67][68]. Our study identified altered expression of seven transcripts putatively associated with GSTs in response to greenbug infestation (Fig.…”
Section: Gsts Peroxidases and Redox State Related Transcriptsmentioning
confidence: 98%
“…The GSTs in plants have antioxidant properties that can scavenge ROS and other toxic compounds, maintain redox homeostasis, and mediate biosynthesis of certain defense molecules; however, specific function vary by the class [66][67][68]. Our study identified altered expression of seven transcripts putatively associated with GSTs in response to greenbug infestation (Fig.…”
Section: Gsts Peroxidases and Redox State Related Transcriptsmentioning
confidence: 98%
“…The protective effect of NO on tolerance to osmotic stress was mediated by GSH in Agropyron cristatum (Shan et al, 2012). NO-dependent changes in the amount and redox potential of glutathione may protect plants from stress-induced injuries directly by the removal of the excess of reactive oxygen species and indirectly by activation of defence mechanisms and adjustment of metabolism to the altered environmental conditions (Noctor et al, 2012). In addition, the role of the other components of redox system in the mediation of the effect of NO on the response to salt stress is indicated by the increased expression of GR and APX in the leaves of maize treated with DETA/NO + NaCl in the present study.…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…However, accumulating evidence demonstrates that GSH is required for the operation of a diverse range of processes that include growth, stress tolerance and cell suicide programs (1,2). Within this context, the requirement for GSH is undoubtedly linked to signalling function, particularly interactions with nitric oxide (NO) and participation in thiol-dependent post-translational protein modifications, which modulate activities, sub-cellular localization, stability or their interactions with partner proteins in plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…It is rather surprising therefore that the nuclear GSH pool is much more resistant to depletion than the cytosolic pool, a property that is particularly important during cell proliferation (5)(6)(7)(8). Although relatively little is known about the nuclear thioredoxins (TRX) and glutaredoxins (GRXs) or their functions in plants (9) it is probable that these redox proteins participate in the plethora of thiol-dependent redox regulation mechanisms and post-translational modifications that are required for plant growth and development, particularly through functions in the nuclei.The many important roles of glutathione in plants have been well documented in recent reviews (1,2,10) and hence the following discussion will focus on how GSH functions as a regulator of plant development, with a particular focus on the nuclear GSH and the regulation of mitosis.…”
mentioning
confidence: 99%